Quantification of flagellar motor stator dynamics through in vivo proton‐motive force control. Issue 2 (10th December 2012) - Tipping, Murray J.; Steel, Bradley C.; Delalez, Nicolas J.; Berry, Richard M.; Armitage, Judith P.
Summary The bacterial flagellar motor, one of the few rotary motors in nature, produces torque to drive the flagellar filament by ion translocation through membrane‐bound stator complexes. We used the light‐driven proton pump proteorhodopsin (pR) to control the proton‐motive force (PMF) in vivo by illumination. pR excitation was shown to be sufficient to replace native PMF generation, and when excited in cells with intact native PMF generation systems increased motor speed beyond the physiological norm. We characterized the effects of rapid in vivo PMF changes on the flagellar motor. Transient PMF disruption events from loss of illumination caused motors to stop, with rapid recovery of their previous rotation rate after return of illumination. However, extended periods of PMF loss led to stepwise increases in rotation rate upon PMF return as stators returned to the motor. The rate constant for stator binding to a putative single binding site on the motor was calculated to be 0.06 s−1. Using GFP‐tagged MotB stator proteins, we found that transient PMF disruption leads to reversible stator diffusion away from the flagellar motor, showing that PMF presence is necessary for continued motor integrity, and calculated a stator dissociation rate of 0.038 s−1.